Demystifying collaborative consumption: a systematic literature review. (11th January 2023) - Dinesh, K.G. Sofi; Rejikumar, G.
Collaborative consumption (CC) is slowly and steadily becoming part and parcel of our economy. People are becoming aware of the benefits of CC, and they are also becoming active participants in CC. Still, research is only a decade old in this area, although the concept of sharing existed before the digital era. This study attempts to give clarity to the idea of collaborative consumption in the light of recent studies and look at its different types, as discussed in the literature. It looks into the major motivating factors and impediments from the consumers' end to engage in collaborative behaviour. There are a lot of areas from the consumer behaviour lens that is open to research in the future, which include quality and value perception in CC, consumer expectation from CC. The review exposes dearth in the literature on conservative geographies where conflict from prevailing social norms and value systems create complexities among customers to engage in active participation to CC.